Improving the outcome of bone marrow transplantation by using CD52 monoclonal antibodies to prevent graft-versus-host disease and graft rejection. - Hale, G; Zhang, M; Bunjes, D; Prentice, H; Spence, D; Horowitz, M; Barrett, A; Waldmann, H (1998)
Graft-versus-host disease (GVHD) is a major cause of mortality and morbidity after allogeneic bone marrow transplantation, but can be avoided by removing T lymphocytes from the donor bone marrow. However, T-cell depletion increases the risk of graft rejection. This study examined the use of CD52 monoclonal antibodies to eliminate T cells from both donor marrow and recipient to prevent both GVHD and rejection. Seventy patients receiving HLA-identical sibling transplants for acute myelogenous leukemia (AML) in first remission were studied. An IgM (CAMPATH-1M) was used for in vitro depletion of the graft and an IgG (CAMPATH-1G) for in vivo depletion of the recipient before graft infusion. No posttransplant immunosuppression was given. Results were compared with two control groups: (1) 50 patients who received bone marrow depleted with CAMPATH-1M, but no CAMPATH-1G in vivo; and (2) 459 patients reported to the International Bone Marrow Transplant Registry (IBMTR) who received nondepleted grafts and conventional GVHD prophylaxis with cyclosporin A (CyA) and methotrexate (MTX). The incidence of acute GVHD was 4% in the treatment group compared with 35% in the CyA/MTX group (P <.001). Chronic GVHD was also exceptionally low in the treatment group (3% v 36%; P <.001). The problem of graft rejection, which had been frequent in the historic CAMPATH-1M group (31%), was largely overcome in the treatment group (6%). Thus, transplant-related mortality of the treatment group (15% at 5 years) was lower than for the CyA/MTX group (26%; P =.04). There was little difference in the risk of leukemia relapse between the treatment group (30% at 5 years) and the CyA/MTX group (29%). Survival of the treatment group at 6 months was better than the CyA/MTX group (92% v 78%), although at 5 years the difference was not significant (62% v 58%) and neither was the difference in leukemia-free survival (60% v 52%). We conclude that T-cell depletion is a useful strategy to prevent GVHD, provided that measures are taken to ensure engraftment. Using CAMPATH-1G to deplete residual host lymphocytes is a simple and practical method to do this. At least in AML, the beneficial reduction in GVHD can be achieved without an increased risk of relapse.